Why Joint Forest Management (JFM) Failed to Deliver? a Case Study of Arjuni Mouza, Midnapore (West Bengal, India) - Mukherjee, Neela (Indian Forester, 1997)
The study discusses the issue from different perspective and arrives at approximate cause of failure of Joint Forest Management in Arjuni Mouza in Midnapore of West Bengal.